1994
DOI: 10.1073/pnas.91.26.12798
|View full text |Cite
|
Sign up to set email alerts
|

The tsA58 simian virus 40 large tumor antigen disrupts megakaryocyte differentiation in transgenic mice.

Abstract: Thrombocytopenia is a condition of multiple etiologies affecting the megakaryocyte lineage. To perturb this lineage in transgenic mice, the tsA58 mutation of the simian virus 40 large tumor antigen was targeted to megakaryocytes using the platelet factor 4 promoter. Ten of 17 transgenic lines generated exhibited low platelet levels, each line displaying a distinct, heritable level of thrombocytopenia. Within a line, the degree of the platelet reduction correlated directly with transgene zygosity. The platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Such mechanisms do not appear to account for the massive accumulation observed in the E2F-1 transgenic mice. Three other mouse models of severe thrombocytopenia that have been described report two-to fourfold increases in bone marrow megakaryocyte numbers (38,44,50), similar to the fivefold increase seen in the E2F-1-expressing mice. However, the E2F-1-expressing mice also have 10-fold increases in the number of splenic megakaryocytes as well as infiltration of megakaryocytes into ectopic sites such as the lymph node and liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mechanisms do not appear to account for the massive accumulation observed in the E2F-1 transgenic mice. Three other mouse models of severe thrombocytopenia that have been described report two-to fourfold increases in bone marrow megakaryocyte numbers (38,44,50), similar to the fivefold increase seen in the E2F-1-expressing mice. However, the E2F-1-expressing mice also have 10-fold increases in the number of splenic megakaryocytes as well as infiltration of megakaryocytes into ectopic sites such as the lymph node and liver.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic lines were screened by using PCR with oligonucleotide primers used for the reverse transcription (RT)-PCR analysis (see below). Homozygous mice were identified as previously described (44).…”
Section: Methodsmentioning
confidence: 99%
“…10 In addition, if a given transgene is not expressed due to regulatory elements within the site of genomic integration, increased numbers of founders need to be generated. 13 Tetracycline-inducible promoters and transactivating mouse lines have been used throughout the literature to circumvent such limitations. A successful application of this system was reported for targeted expression in myeloid cells and hematopoietic progenitors in vivo, [15][16][17][18] but no such study is available for cells in the megakaryocyte/platelet lineage.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, PF4 and other related promoters have been used to examine effects of deregulating the expression of cell-cycle genes, antiapoptotic proteins, receptors, thrombosis-modulating proteins, and others on megakaryocyte/platelet development and/or activity. [4][5][6][7][8][9][10][11][12][13][14] PF4driven constitutive expression is limited, depending on the transgene used, due to occasional lethality during development or adverse effects during adulthood. For instance, Kufrin et al demonstrated that PF4-driven expression of urokinase-type plasminogen activator in mice exhibited a bleeding diathesis, which may have limited the potential number of founder lines that were available for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Both the wild-type and the tsA58 T-proteins induced tumors; the e ect of the thermosensitive protein in vivo is not totally unexpected, as complete inactivation does not occur at the mouse body temperature and tumors are therefore known to result (Robinson et al, 1994).…”
mentioning
confidence: 98%